SEASONAL INCIDENCE OF Rhopalosiphum maidis (Fitch) ON MAIZE CROP IN GUNTUR AND KRISHNA DISTRICTS OF ANDHRA PRADESH - A. Mounika (The Journal of Research ANGRAU, 2024)
The seasonal occurrence of Rhopalosiphum maidis (Fitch) on maize was carried out in the Guntur and Krishna districts of Andhra Pradesh during rabi, 2021-2022 and rabi, 2022-2023. A total of 30 farmer fields were selected from six mandals of maize growing areas viz., Bapatla, Tsunduru, Ponnur, Karlapalem in Guntur district and two mandals viz., Mopidevi and Avanigadda in Krishna district.The population of aphids was recorded at weekly intervals on randomly selected 25 plants of each farmer field from germination to harvesting stage of the crop. The aphids were counted as number of aphids on 1 cm2 leaf area from three leaves (top, middle, lower) of eachplant. The data was statistically analyzed using SPSS for Windows (version 20.0) and Microsoft Excel 2016. In rabi 2021-22 the initial incidence of aphids was commenced from SMW5 (0.21 aphids sq. cm-1) and the highest mean population was recorded in SMW 9 (3.64 aphids sq. cm-1). In rabi 2022-23 the initial incidence was first noticed during SMW4 (1.71 aphids sq. cm-1) and the peak incidence was noticed during SMW 6(4.96 aphids sq. cm-1).The population of aphids showed a positive significant correlation with maximum temperature in both the seasons i.e., rabi, 2021- 22 (r=0.685**) and rabi, 2022-23 (r=0.612*).